Association Study Reveals Genetic Loci Responsible for Arsenic, Cadmium and Lead Accumulation in Rice Grain in Contaminated Farmlands - Liu, Xiuyan; Chen, Sunlu; Chen, Mingxue; Zheng, Guangyong; Peng, Yu; Shi, Xiaoliang; Qin, Ping; Xu, Xiangyang; Teng, Sheng (Frontiers in Plant Science, 2019)
Accumulation of toxic heavy metals and metalloids (THMMs) in crop grain remarkably affects food safety and human health. Reducing the content of THMMs in grain requires the identification and manipulation of the genes regulating their accumulation. This study aimed to determine the genetic variations affecting grain THMM accumulation in rice by using association mapping. We used 276 accessions with 416 K single nucleotide polymorphisms (SNPs) and performed genome-wide association analysis of grain THMM concentrations in rice grown in heavily multi-contaminated farmlands. We detected 22, 17, and 21 quantitative trait loci (QTLs) for grain arsenic, cadmium, and lead concentrations, respectively. Both inter- and intra-subpopulation variants accounted for these QTLs. Most QTLs contained no known THMM-related genes and represented unidentified novel genes. We examined the candidate genes in qGAS1, a QTL for grain arsenic concentration with the best P value detected for the entire population. We speculated that a transport protein of the multidrug and toxin extrusion family could be the candidate gene for this QTL. Our study suggested that the genetic regulation of grain THMM accumulation is very complex and largely unknown. The QTLs and SNPs identified in this study might help in the identification of new genes regulating THMM accumulation and aid in marker-assisted breeding of rice with low grain THMM content.